Double-blind RCT of fish oil supplementation in pregnancy and lactation to improve the metabolic health in children of mothers with overweight or obesity during pregnancy: study protocol - Matire Harwood; José G B Derraik; Wayne S Cutfield; Benjamin B Albert; Justin M O’Sullivan; Gerhard Sundborn; Kathryn Beck; Vidit V Satokar; Karaponi Okasene-Gafa; David Cameron-Smith; Shikha Pundir; R Preston Mason (BMJ Open, 2020)
Introduction Maternal obesity during pregnancy is associated with adverse changes in body composition and metabolism in the offspring. We hypothesise that supplementation during pregnancy of overweight and obese women may help prevent the development of greater adiposity and metabolic dysfunction in children. Previous clinical trials investigating fish oil supplementation in pregnancy on metabolic outcomes and body composition of the children have not focused on the pregnancies of overweight or obese women.Methods and analysis A double-blind randomised controlled trial of fish oil (providing 3 g/day of n-3 polyunsaturated fatty acids) versus an equal volume of olive oil (control) taken daily from recruitment until birth, and in breastfeeding mothers, further continued for 3 months post partum. Eligible women will have a singleton pregnancy at 12–20 weeks’ gestation and be aged 18–40 years with body mass index ≥25 kg/m2 at baseline. We aim to recruit a minimum of 128 participants to be randomised 1:1. Clinical assessments will be performed at baseline and 30 weeks of pregnancy, including anthropometric measurements, fasting metabolic markers, measures of anxiety, physical activity, quality of life and dietary intake. Subsequent assessments will be performed when the infant is 2 weeks, 3 months and 12 months of age for anthropometry, body composition (dual-energy X-ray absorptiometry (DXA)) and blood sampling. The primary outcome of the study is a between-group difference in infant percentage body fatness, assessed by DXA, at 2 weeks of age. Secondary outcomes will include differences in anthropometric measures at each time point, percentage body fat at 3 and 12 months and homeostatic model assessment of insulin resistance at 3 months. Statistical analysis will be carried out on the principle of intention to treat.Ethics and dissemination This trial was approved by the Northern A Health and Disabilities Ethics Committee, New Zealand Ministry of Health (17/NTA/154). Results will be published in a peer-reviewed journal.Trial registration number ACTRN12617001078347p; Pre-results.